2003
DOI: 10.1089/10966200360716553
|View full text |Cite
|
Sign up to set email alerts
|

Chemopreventive Effects of Pomegranate Seed Oil on Skin Tumor Development in CD1 Mice

Abstract: Pomegranate seed oil was investigated for possible skin cancer chemopreventive efficacy in mice. In the main experiment, two groups consisting each of 30, 4-5-week-old, female CD(1) mice were used. Both groups had skin cancer initiated with an initial topical exposure of 7,12-dimethylbenzanthracene and with biweekly promotion using 12-O-tetradecanoylphorbol 13-acetate (TPA). The experimental group was pretreated with 5% pomegranate seed oil prior to each TPA application. Tumor incidence, the number of mice con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(102 citation statements)
references
References 15 publications
5
96
0
1
Order By: Relevance
“…Pomegranate juice and extracts have been shown to have potent in vitro antioxidant [7,24] and in vivo anti-atherosclerotic properties [8,9,15], attributed to its high content of polyphenols including ETs and EA. Recently, there have also been numerous reports on the in vitro and in vivo anticancer properties of pomegranates [10,[25][26][27][28][29][30]. The major pomegranate ET, punicalagin, is reported as the active ingredient responsible for N 50% of the juice's antioxidative potential [7,24] and can reach levels of N2 g/L of juice [7].…”
Section: Discussionmentioning
confidence: 99%
“…Pomegranate juice and extracts have been shown to have potent in vitro antioxidant [7,24] and in vivo anti-atherosclerotic properties [8,9,15], attributed to its high content of polyphenols including ETs and EA. Recently, there have also been numerous reports on the in vitro and in vivo anticancer properties of pomegranates [10,[25][26][27][28][29][30]. The major pomegranate ET, punicalagin, is reported as the active ingredient responsible for N 50% of the juice's antioxidative potential [7,24] and can reach levels of N2 g/L of juice [7].…”
Section: Discussionmentioning
confidence: 99%
“…Pomegranate polyphenols are potent antioxidants which have been shown both in vitro and in vivo to inhibit the growth of prostate and some other forms of cancer [10][11][12][13][14][15]. Our group has demonstrated that 8 ounces of pomegranate juice consumed daily following primary treatment of prostate cancer significantly prolonged prostate specific antigen (PSA) doubling time from 15 months to 54 months [30].…”
Section: Discussionmentioning
confidence: 99%
“…Sample RNA content was quantified by measuring the absorbance at 260 nm with a Gene Quant Spectrophotometer (Amersham-Pharmacia Biotech, Piscataway, NJ). Reverse transcription was performed on 3 μg of RNA by using oligo(dT) [12][13][14][15][16][17][18] primers (Invitrogen) with SuperScript III Reverse Transcriptase (Invitrogen) according to the manufacturer's instruction.…”
Section: Rna Extraction and Reverse Transcriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estudos na literatura estabeleceram a importância da atividade quimiopreventiva da P. granatum contra a incidência e a multiplicação tumoral (Kim et al, 2002;Hora et al, 2003).…”
Section: Figura 2 Viabilidade Celular De Células Ascíticas Do Tumor Deunclassified